Editorial - Villaruz, Basilio Esteban S. (Musika Jornal; No 6 (2010), 2010)
Traversing and Transforming Sounds and Spaces Today This issue courts the distinction of crossing disciplines and cultural or social divides, some modern media facilitating--to varying valuations.